Gymnothorax pseudotile sp. nov. (Muraenidae: Muraeninae) from Bay of Bengal India - Mohapatra, Anil; Smith, David G.; Ray, Dipanjan; Mishra, Subhrendu Sekhar; Mohanty, Swarup Ranjan (Zootaxa, 2017)
Gymnothorax pseudotile sp. nov., is described based on nine specimens (337–503 TL) collected from the northern Bay of Bengal. The species has intermaxillary teeth in three longitudinal rows, consisting of a median row of three depressible fang-like teeth and a single row of 6 teeth on each side; dorsal-fin origin above the posterior half of the gill opening; both dorsal and anal fin low with pale margin; predorsal vertebrae 12–13, preanal vertebrae 56–59, total vertebrae 126–129 (MVF: 13-58-128). The closely-related Gymnothorax tile, for which a brief description is included, can be differentiated from the new species by having teeth moderately stout, intermaxillary teeth in 5 rows; dorsal-fin origin over or slightly before the gill opening; dorsal and anal fins high with a pale margin, and predorsal vertebrae 9–11.